The lncRNA H19 Promotes Cell Proliferation by Competitively Binding to miR-200a and Derepressing β-Catenin Expression in Colorectal Cancer. (10th January 2017) - Yang, Weiwei; Ning, Ning; Jin, Xiaoming
Abstract : H19, a paternally imprinted noncoding RNA, has been found to be overexpressed in various cancers, including colorectal cancer (CRC), and may function as an oncogene. However, the mechanism by which H19 regulates CRC progression remains poorly understood. In this study, we aimed to assess H19 expression levels in CRC tissues, determine the effect of H19 on CRC proliferation, and explore the mechanism by which H19 regulates the proliferation of CRC. We measured H19 expression using qRT-PCR and analysed the effects of H19 on colon cancer cell proliferation via cell growth curve, cell viability assay, and colony formation assays. To elucidate the mechanism underlying these effects, we analysed the interactions between H19 and miRNAs and identified the target gene to which H19 and miRNA competitively bind using a series of molecular biological techniques. H19 expression was upregulated in CRC tissues compared with adjacent noncancerous tissues. H19 overexpression facilitated colon cancer cell proliferation, whereas H19 knockdown inhibited cell proliferation. miR-200a bound to H19 and inhibited its expression, thereby decreasing CRC cell proliferation. β -Catenin was identified as a target gene of miR-200a. H19 regulated β -catenin expression and activity by competitively binding to miR-200a. H19 promotes cell proliferation by competitively binding to miR-200a and derepressing β -catenin in CRC.